Towards the development of research skills of Physics students through the use of simulators: a case study - Angulo Silva, Edwin Wilber (2023)
The objective of this research is to evaluate the impact of using the simulators on students’ achievement of competencies, such as: Inquire, through scientific methods to build knowledge. The methodology used consisted of qualitative research whose data collection was carried out through an experiment with interactive Physics Educational Technology (PhET) simulators. The experiment was carried out through a simple random sampling of 25 students from a population of 100 students of physics subjects. With this sample, four learning sessions were developed using the PhET interactive simulator, which were implemented in a way that helped the development of skills according to learning indicators oriented to the achievement of the competence, Inquire, through scientific methods to build knowledge. A pretest and a posttest were applied. The results of the study show the benefits of the use of simulators in the teachinglearning processes, contributing to the achievement of the competence inquire, through scientific methods to build knowledge, developing capacities, such as: Problematize situations to inquire, design strategies to inquire, generate and record data or information, analyze data and information, and evaluate and communicate the process and results of their inquiry. In conclusion, 100% of the students develop inquiry competencies through the development of capabilities.